2021
DOI: 10.1186/s12912-021-00571-w
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ perception of patient safety culture and its relationship with adverse events: a national questionnaire survey in Iran

Abstract: Background Patient safety culture is an important factor in determining hospitals’ ability to address and reduce the occurrence of adverse events (AEs). However, few studies have reported on the impact of nurses’ perceptions of patient safety culture on the occurrence of AEs. Our study aimed to assess the association between nurses’ perception of patient safety culture and their perceived proportion of adverse events. Methods A cross-sectional surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(89 citation statements)
references
References 42 publications
3
54
3
1
Order By: Relevance
“…The second high dimension was teamwork within units of 86% score, which was similar to the results from previous studies [19][20][21][22][23][24]. Nurses in this hospital believe that good teamwork is crucial for improving patient safety culture.…”
Section: Discussionsupporting
confidence: 85%
“…The second high dimension was teamwork within units of 86% score, which was similar to the results from previous studies [19][20][21][22][23][24]. Nurses in this hospital believe that good teamwork is crucial for improving patient safety culture.…”
Section: Discussionsupporting
confidence: 85%
“…The prevalence of adverse events in ED is higher and varied from 4 to 68% [ 3 ]. According to a study by Kakemam et al, the prevalence of adverse events in Iran is between 7 and 40% [ 4 ]. Lower adverse events and better patient care safety are usually the outcomes of perceived teamwork [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…But it was lower than another conducted study in Iran, which showed that the experience of occurrence of AEs by nurses in the past 6 months was 48% (Kakemam, Hajizadeh, et al, 2021). Evidence has demonstrated that many factors can be attributed to the AEs occurrence, such as heavy workload, inappropriate shifting, less unsuccessful cognition, long working hours, job stress, weak teamwork and poor patient safety (Kakemam et al, 2019; Kakemam, Gharaee, et al, 2021; Kakemam, Hajizadeh, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Another national survey conducted by Kakemam, Gharaee, et al (2021) showed that the occurrence AEs varied between 51.2% and 63.0% in the last 12 months. In addition, 29.1% of nurses in a national study reported that they had experienced AEs in the past half-year (Kakemam et al, 2019).…”
Section: Introductionmentioning
confidence: 99%